2017
DOI: 10.1177/1470320317717831
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR/p70S6K1 signaling pathway in renal fibrosis of children with immunoglobulin A nephropathy

Abstract: Aim:The purpose of this study was to explore whether mTOR/p70S6K1 signaling is activated in renal fibrosis of immunoglobulin A nephropathy.Methods:Seventy-two children with immunoglobulin A nephropathy were divided into three groups according to their clinical features and pathological grades. Six normal renal specimens were included in the control group. The expression levels of angiotensin II, mTOR, p70S6K1, E-cadherin, and α-smooth muscle actin in renal tissues were determined by immunohistochemistry method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…It was reported in the literature that VEGF bound to its receptor VEGFR and then triggered a series of disorders of intracellular signal transduction pathways such as PI3K/AKT [ 14 ], Ras/MAPK [ 15 ], NOS [ 16 ], PKC [ 17 ], and FAK/Paxillin [ 18 ], resulting in vascular endothelial cell proliferation, cell survival, cell migration, cytoskeletal rearrangement, vascular penetration, and other processes. In addition, it was said that the expressions of phosphorylated ERK [ 19 ], AKT [ 20 ], mTOR [ 21 ], and FAK [ 22 ] were significantly higher in proliferative hemangioma than that in regressive period and normal skin tissues. These researches show that the above signaling molecules are involved in the proliferation of hemangioma, which may be the main activation signal of hemangioma proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in the literature that VEGF bound to its receptor VEGFR and then triggered a series of disorders of intracellular signal transduction pathways such as PI3K/AKT [ 14 ], Ras/MAPK [ 15 ], NOS [ 16 ], PKC [ 17 ], and FAK/Paxillin [ 18 ], resulting in vascular endothelial cell proliferation, cell survival, cell migration, cytoskeletal rearrangement, vascular penetration, and other processes. In addition, it was said that the expressions of phosphorylated ERK [ 19 ], AKT [ 20 ], mTOR [ 21 ], and FAK [ 22 ] were significantly higher in proliferative hemangioma than that in regressive period and normal skin tissues. These researches show that the above signaling molecules are involved in the proliferation of hemangioma, which may be the main activation signal of hemangioma proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zhang et al have reported that the mTOR signaling pathway is involved in the proliferation of mesangial cells due to IgA1 isolated from HSP patients, most likely related to the mesangial injury of HSPN [ 30 ]. Furthermore, Xu et al have shown that the mTOR signaling pathway is activated in renal tissues of children with immunoglobulin A nephropathy [ 31 ]. Another classification identified in this study was the SWI/SNF superfamily-type complex, and it was found to be active during the progression of HSPN from type 1 to type 2 (Supplementary Table S 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In renal disease, mTOR has been identified as a potential therapy target [32]. Previous studies also indicated that mTOR played a key role in renal fibrosis [33, 34]. However, in different organs, microenvironments, and study objects, the role of mTOR showed an obvious heterogeneity.…”
Section: Discussionmentioning
confidence: 99%